1999
DOI: 10.1063/1.371270
|View full text |Cite
|
Sign up to set email alerts
|

Coevaporated Cu–In films as precursors for solar cells

Abstract: We investigate Cu–In thin films used as precursors for the production of CuInS2 and Se2 solar-cell absorber material via reactive annealing. The films are produced by coevaporation of Cu and In onto glass substrates and are characterized by means of Rutherford backscattering and x-ray diffraction (XRD). The interplay of phase composition, morphology, and surface topography is studied as a function of chemical composition, substrate temperature, and annealing processes. The analysis of the XRD data is based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…The XRD pattern shown in Fig. 1(c) elucidates that the Cu-In nanoparticles contain the two main phases of In (tetragonal, JCPDS-65-9682) and Cu 11 In 9 (monoclinic, JCPDS-65-4963), which is consistent with the previous report that stable component phases of Cu-In alloy above 150 • C are mainly In and Cu 11 In 9 [17]. In fact, we obtain the two component phases at a relative lower temperature of 140 • C. The obtained Cu-In nanoparticles are bigger in sizes due to the inter-diffusion of Cu and In nanoparticles [18], as indicated from the SEM image of a Cu-In metal film in Fig 4(a).…”
Section: B(oh) 3 /Bhsupporting
confidence: 90%
“…The XRD pattern shown in Fig. 1(c) elucidates that the Cu-In nanoparticles contain the two main phases of In (tetragonal, JCPDS-65-9682) and Cu 11 In 9 (monoclinic, JCPDS-65-4963), which is consistent with the previous report that stable component phases of Cu-In alloy above 150 • C are mainly In and Cu 11 In 9 [17]. In fact, we obtain the two component phases at a relative lower temperature of 140 • C. The obtained Cu-In nanoparticles are bigger in sizes due to the inter-diffusion of Cu and In nanoparticles [18], as indicated from the SEM image of a Cu-In metal film in Fig 4(a).…”
Section: B(oh) 3 /Bhsupporting
confidence: 90%
“…All three types of samples originally consisted of CuIn 2 and Cu, as was already reported in Refs. [7,10] due to the reaction Cu solid +2In solid -CuIn 2 taking place above À33 1C [5]. In accordance with the overall composition of the films, the concentration of free Cu is decreasing with the decreasing Cu/In ratio.…”
Section: Discussionmentioning
confidence: 73%
“…These phases may be metastable modifications of the Z-Cu 16 In 9 phase and its high-temperature modification Z 0 . In a recent work, Gossla et al [7] were able to prepare all phases which are stable at room temperature using co-evaporation of Cu x In layers. Using in situ high-energy powder diffraction, Brummer et al [8] have investigated the Cu-In phase transformations with 60 sec time resolution.…”
Section: Introductionmentioning
confidence: 99%
“…CuInS 2 (CIS) with the band gap value of 1.5 eV and its high absorption coefficient of almost 10 5 cm −1 is representing an important class of the recently developed light absorbers for highly efficient and lowcost solar cells [1][2][3]. Recent studies have shown that CIS solar cell efficiency ranges from 10.2 to 12.3% [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most commonly used methods is a two-step process. The first step is the production of a precursor Cu-In film by evaporating [10] or sputter deposition [11] in a vacuum system. In the second step, the precursor film is placed in a sulfurisation furnace filled with H 2 S gas or elemental sulfur vapour for the formation of a CIS film.…”
Section: Introductionmentioning
confidence: 99%